You can't afford to get sick : your guide to optimum health and health care - Weil, Andrew (New York : A Plume Book, 2009)
The World Health Organization recently rated America thirty-seventh in health outcomes, on par with Serbia. Tackling head-on the three major myths of American medicine, Dr. Weil shows how medical schools fail to give future doctors the education they need to care for patients, how insurance companies have destroyed our opportunity to get excellent care, and how pharmaceutical companies have come to rule our lives. The solution involves nothing less than the creation of a completely new culture of health and medicine in this country.--From publisher description.
Includes bibliographical references and index.
Keywords: Health care reform -- United States; Medical education -- United States; Health insurance -- United States; Pharmaceutical industry